Repurchase Intention Based On E-Service Quality And Customer Trust At Three Top Brand E-Commerce Indonesia - Sherli Junianingrum; Nanang Apriliyanto; Lukman Zaini Abdullah (LPPM ISNJ Bengkalis, 2023)
E-commerce is of particular concern to the shopping culture in Indonesia. However, there are weaknesses such as inconsistent product quality, high shipping costs, and fraud, so e-commerce has significant obstacles to attracting customers' interest in buying again. This research analyzes customer repurchase interest based on e-service quality and customer trust. This type of research is causality research using a quantitative approach. The population of this research is all Tokopedia, Shope, and Lazada consumers in Indonesia. The research sample used a purposive sampling method with a final total of 200 respondents. The data analysis method uses structural equation modelling (SEM) analysis, tested using SmartPLS. This research results in E-service quality positively and significantly affecting customer trust and repurchase interest. Customer trust positively and significantly affects repurchase interest. Customer trust can mediate the influence of e-service quality on repurchase interest. The results of this research contribute to developing and refining theories related to repurchase interest in e-commerce platforms in Indonesia and filling gaps in several studies that have never described the object of this research.